Maintain Madura language in Manduro Village, Jombang, East Java - M Khoirunnada (Journal of Research in Business, Economics, and Education, 2020)
This study examines the maintenance of Madurese language in Manduro Village. The focus of this research is the use of Madurese (BM) and Javanese (BJ) in the family realm according to the age group of the respondents. All Madurese speakers in Manduro Village became the study population, while the sample was limited to 88 respondents who were randomly selected and divided into four age groups consisting of ages 10 - 13 years, 14 - 24 years, 25 - 50 years, and 50 years old. on. This research is based on the realm theory of Fishman (1972c) and Greenfield (1972), and the preservation of language from Holmes (2013). The method used is quantitative. The data were obtained by applying a survey questionnaire technique. Data were analyzed using compare means analysis to determine the mean score of the use of Madurese (BM) and Javanese (BJ) based on age groups. In general, the results of this study indicate that the use of BM by the Manduro community is still being maintained. This result is based on obtaining an overall mean score of 1.96 ((range of scores between 1 - 5, where 1 = (almost) always BM, 2 = often BM, 3 = balanced BM and BJ, 4 = frequent BJ, and 5 = (almost) always BJ)). (Almost) always using BM occurs in respondents aged 50 years and over and 25 - 50 years, meanwhile those aged 14-24 years tend to use BM more often than BJ, while those aged 10-13 years are balanced in using BM and BJ.